Renewable energy from palm oil mill effluent (Pome) using microbial fuel cell - Noraziah, Binti Abdul Wahab (Universiti Malaysia Sarawak, UNIMAS, 2008)
As fossil fuel becomes finite, the growing pressure is on finding and sustaining renewable energy. Renewable energy sources are from solar, wind hydraulic, biomass and fuel cell. The Malaysian government has nominated renewable energy as its fifth fuel strategy, in addition to the current fuel strategy that is oil, natural gas, coal and hydropower, by 2020. With the development of Sarawak Corridor of Renewable Energy (SCORE) in the country, the sources should be harnessed to produce renewable energy and to prevent harmful biogas released to the environment. The purpose of this research was to examine the potential of palm oil mill effluent (POME) as a substrate to Microbial Fuel Cell (MFC). MFC is system that converts organic matter into energy. The research was carried out by studying the viability of POME to generate power density in batch mode and at varied feed rates of continuous flow in the MFS system.